An assessment of one year of computer-assisted microbiology reporting at Charing Cross Hospital. Issue 3 (March 1974) - Andrews, H. J.; Vickers, M.
Abstract : The pilot scheme began in August 1972 after three months of running parallel with a conventional system. In October 1972 the system was moved from Fulham Hospital into the new Charing Cross Hospital. Sixty thousand routine bacteriology requests have been processed satisfactorily by the computer system, about 70% of the total received. The cost for a computer-printed report is 32p compared with 6p for a typed one.